Pediatric neurodevelopment by prenatal Zika virus exposure: a cross-sectional study of the Microcephaly Epidemic Research Group Cohort - Paula Fabiana Sobral da Silva; Sophie Helena Eickmann; Ricardo Arraes de Alencar Ximenes; Ulisses Ramos Montarroyos; Marilia de Carvalho Lima; Celina M. Turchi Martelli; Thalia Velho Barreto de Araújo; Elizabeth B. Brickley; Laura Cunha Rodrigues; Fabiana Cristina Lima da Silva Pastich Gonçalves; Maria Durce Costa Gomes Carvalho; Wayner Vieira de Souza; et al. (BMC, 2020)
Abstract Background The implications of congenital Zika Virus (ZIKV) infections for pediatric neurodevelopment and behavior remain inadequately studied. The aim of this study is to investigate patterns of neurodevelopment and behavior in groups of children with differening severities of ZIKV-related microcephaly and children with prenatal ZIKV exposure in the absence of microcephaly. Methods We conducted a cross-sectional study, nested in a cohort, of 274 children (aged 10-45 months) who were born during the peak and decline of the microcephaly epidemic in Northeast Brazil. Participants were evaluated between February 2017 and August 2019 at two tertiary care hospitals in Recife, Pernambuco, Brazil. We analyzed the children in four groups assigned based on clinical and laboratory criteria: Group 1 had severe microcephaly; Group 2 had moderate microcephaly; Group 3 had prenatal ZIKVexposure confirmed by maternal RT-PCR testing but no microcephaly; and Group 4 was a neurotypical control group. Groups were evaluated clinically for neurological abnormalities and compared using the Survey of Wellbeing of Young Children (SWYC), a neurodevelopment and behavior screening instrument validated for use in Brazil. Children with severe delays underwent further evaluation with an adapted version of the SWYC. Results Based on the SWYC screening, we observed differences between the groups for developmental milestones but not behavior. Among the 114 children with severe microcephaly of whom 98.2% presented with neurological abnormalities, 99.1% were 'at risk of development delay' according to the SWYC instrument. Among the 20 children with moderate microcephaly of whom 60% presented with neurological abnormalities, 65% were 'at risk of development delay'. For children without microcephaly, the percentages found to be 'at risk of developmental delay' were markedly lower and did not differ by prenatal ZIKV exposure status: Group 3 (N = 94), 13.8%; Group 4 (N = 46), 21.7%. Conclusions Among children with prenatal ZIKV exposure, we found a gradient of risk of development delay according to head circumference. Children with severe microcephaly were at highest risk for delays, while normocephalic ZIKV-exposed children had similar risks to unexposed control children. We propose that ZIKV-exposed children should undergo first-line screening for neurodevelopment and behavior using the SWYC instrument. Early assessment and follow-up will enable at-risk children to be referred to a more comprehensive developmental evaluation and to multidisciplinary care management.